Standing Postural Control in Individuals with Autism Spectrum Disorder: Systematic Review and Meta-analysis - Lim, Y.; Partridge, K.; Girdler, S.; Morris, Susan (Springer New York LLC, 2017)
Impairments in postural control affect the development of motor and social skills in individuals with autism spectrum disorder (ASD). This review compared the effect of different sensory conditions on static standing postural control between ASD and neurotypical individuals. Results from 19 studies indicated a large difference in postural control between groups across all sensory conditions. This review revealed sensorimotor and multiple sensory processing deficits in ASD. The tendency for individuals with ASD to be more susceptible to postural instability with use of visual information compared with somatosensory information suggests perinatal alterations in sensory development. There is further scope for studies on the use of sensory information and postural control to provide additional evidence about sensorimotor processing in ASD.